Prevalence of Gastrointestinal Symptoms and Clinical Outcomes in Hospitalized Coronavirus Disease 2019 Patients: A Single-Center Study from Turkey - Dolu, Süleyman; Bengi, Göksel; Avkan-Oğuz, Vildan; Tertemiz, Kemal Can; Gezer, Naciye Sinem; Çavuş, Sema Alp; Alpaydın, Aylin Özgen; Kuruüzüm, Ziya; Ergan, Begüm; Sevinç, Can; et al. (Turkish Journal of Gastroenterology, 2022)
Background: In patients with coronavirus disease 2019, the gastrointestinal symptoms have been reported increasingly in addition to the respiratory system symptoms. The studies show that the prevalence of gastrointestinal system symptoms and how the gastrointestinal system contributes to the severity and prognosis of the disease is still not clear. This study aims to find the prevalence of gastrointestinal symptoms and the correlation between the gastrointestinal symptoms and the clinical results in hospitalized patients diagnosed with coronavirus disease 2019. Methods: This study retrospectively analyzes patients diagnosed with coronavirus disease 2019 and hospitalized in the pandemic unit between March 2020 and August 2020 and compares their demographic and clinical characteristics, laboratory and radiologic findings, coronavirus disease 2019 treatments received, the clinical course of the disease, and the gastrointestinal symptoms. Results: In our study, we included 322 patients diagnosed with coronavirus disease 2019 and hospitalized; 39 patients (12.1%) were admitted to the hospital with at least one gastrointestinal symptom (nausea and vomiting, diarrhea, abdominal pain, and the loss of taste). Nausea and vomiting are the most common gastrointestinal symptoms with a prevalence of 7.1%, followed by diarrhea with 2.8%, the loss of taste with 2.2%, and abdominal pain with 1.5%. The mean age and D-dimer levels of the patients showing gastrointestinal symptoms were lower than those who did not have any gastrointestinal symptoms. We did not find a significant correlation between the presence of the gastrointestinal symptoms and the severity of the disease, treatment received, risk of acute respiratory distress syndrome and septic shock, admission to the intensive care unit, the need for mechanical ventilation, the mortality rate or the length of hospitalization in the medical floor or the intensive care unit. Conclusion: In this study, we observed that 12.1% of coronavirus disease 2019 patients apply to the hospital due to gastrointestinal symptoms. Furthermore, the gastrointestinal symptoms do not seem to affect the severity and the course of the disease, it is important to identify coronavirus disease 2019 patients showing unusual symptoms such as the gastrointestinal symptoms at an early stage to protect healthcare professionals from infection risk. Cite this article as: Dolu S, Bengi G, Avkan-Oğuz V, et al. Prevalence of gastrointestinal symptoms and clinical outcomes in hospitalized coronavirus disease 2019 patients: A single-center study from Turkey. Turk J Gastroenterol. 2022;33(11):955-963.